Non-inclusive tribal workforce participation in urban spaces: A case study of Jharkhand - Kumar, Bipin; Baraik, Vijay Kumar (National Geographical Journal of India, 2022)
Tribals, as indigenous communities, have always been subject to neglect and marginalisation. The noninclusive economic mobility is the enduring legacy of ethnic segregations and discriminations. In the development framework, their inclusion into the fast-urbanizing urban spaces is considerably an unexplored question. In this backdrop, the paper looks at tribals’ economic mobility in the urban spaces of Jharkhand through occupational classes. The paper is based on the 21-fold industrial classification provided in B-Series tables by Census of India, 2011. It uses a simple statistical method to analyse the occupational structure, sectoral participation and economic mobility. The paper portrays an assorted picture, inapt to the claim of an inclusive development model. The tribals have hardly been successful in catching the neo-liberal market-led economic opportunities, as the most developed urban centres are barely in tandem with the higher workforce participation in secondary and tertiary sectors; especially in the formal sectors. The other contrasting scenario is the least developed urban spaces have a higher level of tribal workforce participation in the tertiary sector than their most developed counterparts